ANALISIS ABNORMAL RETURN SEBELUM DAN SESUDAH EX-DATE DIVIDEN PADA PERUSAHAAN IDX30 DI BEI - Kevin Syach Putra Suhendi (2021)
One of the reasons for investors to invest in a stock is the dividend distribution by the company. Dividend announcements can be good information for investors if the dividends the company distributes increase. On the other hand, it will be bad information for investors if the dividends distributed by the company decrease. Regarding dividend announcement information, is this dividend announcement one of the information that can make a significant difference in abnormal returns. The purpose of this research is to determine the differences in abnormal returns before and after the ex-dividend date at the IDX30 company which announced the dividend increase and to find out the difference in abnormal returns before and after the ex-dividend date at the IDX30 company which announced the dividend reduction. The population of this study is stocks included in the IDX30 period 2018-2019. The sample of this study used a purposive sampling technique which resulted in 16 companies announcing dividend increases and 11 companies announcing dividend decreases. This type of research is a quantitative research. The data used are historical price data / stock prices 10 days before and 10 days after the ex-dividend date obtained from the Yahoo Finance website. The data analysis technique used the event study method and paired sample t-test. The results showed (1) There was no significant abnormal return before and after the ex-dividend date on the company IDX30 which announced the dividend increase. (2) There is no significant difference in abnormal returns before and after the ex-dividend date on company IDX30 which announces dividend reduction. The conclusion is that dividend announcements are not the only information that has an impact on investors in valuing a stock but is determined by the earning power of the assets owned by the company. Keywords: Abnormal Return, Ex-Dividend Date, IDX30, Dividend Increase, Dividend Decrease.